PENGARUH PERGANTIAN MANAJEMEN, OPINI AUDIT, FINANCIAL DISTRESS DAN PERTUMBUHAN PERUSAHAAN KLIEN TERHADAP AUDITOR SWITCHING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2017) (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine how: 1) the influence of management change onthe auditor switching 2) the influence of audit opinion on the auditor switching 3)the influence of financial distress on the auditor switching 4) the influence of thegrowth of the client company on the auditor switching. The sample used in thisstudy consisted of 75 samples of manufacturing companies listed on the IndonesiaStock Exchange during 2015-2017. The sample in this study was taken using apurposive sampling method. Data analysis method uses logistic regressionanalysis (Logistic Regression) with the help of a computer program, namely SPSSversion 22.0. The results showed that: 1) Management Change has a positiveeffect on auditor switching with a significant value of 0.048 <0.05 2) AuditOpinion has a positive effect on auditor switching with a significant value of 0.00<0.05 3) Financial Distress has a positive effect on significant value of 0.027<0.05 4) Client Company Growth has no effect on auditor switching with asignificant value of 0.146> 0.05.Keywords : Switching Auditor, Management Change, Audit Opinion, FinancialDistress, and Client Company Growth